Cation-exchanged zeolites for the selective oxidation of methane to methanol. Issue 1 (27th October 2017) - Kulkarni, Ambarish R.; Zhao, Zhi-Jian; Siahrostami, Samira; Nørskov, Jens K.; Studt, Felix
Abstract : Development of an ideal methane activation catalyst presents a trade-off between stability and reactivity of the active site that can be achieved by tuning the transition metal cation, active site motif and the zeolite topology. Abstract : Motivated by the increasing availability of cheap natural gas resources, considerable experimental and computational research efforts have focused on identifying selective catalysts for the direct conversion of methane to methanol. One promising class of catalysts are cation-exchanged zeolites, which have steadily increased in popularity over the past decade. In this article, we first present a broad overview of this field from a conceptual perspective, and highlight the role of theory in developing a molecular-level understanding of the reaction. Next, by performing and analyzing a large database of density functional theory (DFT) calculations for a wide range of transition metal cations, zeolite topologies and active site motifs, we present a unifying picture of the methane activation process in terms of active site stability, C–H bond activation and methanol extraction. Based on the trade-offs of active site stability and reactivity, we propose a framework for identifying new, promising active site motifs in these systems. Further, we show that the high methanol selectivity arises due to the strong binding nature of the C–H activation products. Finally, using the atomistic and mechanistic insight obtained from these analyses, we summarize the key challenges and future strategies for improving the performance of cation-exchanged zeolites for this industrially relevant conversion.